Determination of UV-Vis Spectrophotometric Method of Metal Complexes Stoichiometry between Cu (II) and Zn (II) with Vilazodone Hydrochloride - (:unkn) unknown (INT JOURNAL PHARMACEUTICAL RESEARCH & ALLIED SCIENCES, 2018)
In the presenst research work, simple, precise and accurate UV-Vis spectrophotometric method was developed for the determination of metal complexes stoichiometry of Cu(II)-Vilazodone Hydrochloride and Zn(II)-Vilazodone Hydrochloride. The separate spectrums of Vilazodone Hydrochloride and the complexes occured between Cu(II) and Zn(II). Metal ions were taken in ultra-violet area, and the stoichiometric ratios of the complexes occured between Vilazodone Hydrochloride with Cu(II) and Zn(II) metal ions. The stoichiometry of these complexes were also determined by using mole ratio method of Cu(II)-Vilazodone Hydrochloride and Zn(II)-Vilazodone. Hydrochloride were calculated as 1:1. Vilazodone Hydrochloride's recovery was 97.1%. Lambert-Beer 's obeyed the concentration range of 2.40-12.0 mu g/mL for Vilazodone Hydrochloride. The LOD and LOQ were found to be 2.93 and 13.67 mu g/mL for Vilazodone Hydrochloride; respectively. The interaction between the Vilazodone Hydrochloride-Cu (II) and Vilazodone Hydrochloride-Zn (II) was investigated by applying this spectrophotometric method, and satisfactory results were obtained.
Keywords: Vilazodone Hydrochloride; Metal complex; Mole ratio method; Stoichiometry